Sacred nominations in texts about national liberation movement of Ukraine: a comparative approach - Bachun, Liliya (Current issues of Ukrainian linguistics: theory and practice, 2021)
The article describes the main provisions of the theolinguistic science, its defining criteria and objects of further research. Theoretical bases of the concept of religious discourse and its connection with ethnocentrism of the analyzed material have been stated. A comparative analysis of the peculiarities of the semantic-associative motivation for use of sacred-type coreferents in the twelve texts of works about the national liberation movement of Ukraine with their functioning in the text of the Bible have been conducted. Categorically analyzed names of the sacred coreferents have been divided according to the eschatological-ontological connotative directions, designations of religious things of use and the names of passional sacral type. Nine names of biblical anthroponyms have been singled out in the analyzed twelve texts of works about the national liberation movement of Ukraine, which determine the objectification of the sacred conceptosphere. The variable component of the biblical anthroponyms functioning (St. Peter, Joseph of Arimathea and John the Baptist) in the analyzed texts of works about the national liberation movement of Ukraine and their various translations of the Bible have been clarified. The functional and stylistic features of the writers' usage of Old Testament and New Testament precedent biblical names and their common and distinctive features of functioning in the texts of various translations of the Bible have been highlighted. The category of the sacred onyms′ functionality has been realized through the words′ connotative-associative layers (Jeremiah and lexical units of weeping, sobbing; King David ‒ psalms), comparison (Moses ‒ Ivan Franko), the characteristics of activities (betrayal of Judas) and identification of Adam with the Fall, and Christ with eternal life.
Keywords: connotation, concept, coreferent, religious linguistics, theolinguistics, precedent biblical anthroponym